2017
DOI: 10.1145/3092368
|View full text |Cite
|
Sign up to set email alerts
|

Mo(bile) Money, Mo(bile) Problems

Abstract: Mobile money, also known as branchless banking, leverages ubiquitous cellular networks to bring much-needed financial services to the unbanked in the developing world. These services are often deployed as smartphone apps, and although marketed as secure, these applications are often not regulated as strictly as traditional banks, leaving doubt about the truth of such claims. In this article, we evaluate these claims and perform the first in-depth measurement analysis of branchless banking applications. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
0
42
0
2
Order By: Relevance
“…They describe five factors which contribute to these differences, including the prevalence of text message banking and piracy in the developing world. More recently, security researchers have studied apps used for mobile banking in the developing world and found them rife with technical security vulnerabilities ( Reaves et al, 2015 ). While similar problems are present in apps created for and used by people in the developed world, this work echoes the findings of ( Ben-David et al, 2011 ) that the prevalence of these factors in the developing world increases the potential reach of their effects.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…They describe five factors which contribute to these differences, including the prevalence of text message banking and piracy in the developing world. More recently, security researchers have studied apps used for mobile banking in the developing world and found them rife with technical security vulnerabilities ( Reaves et al, 2015 ). While similar problems are present in apps created for and used by people in the developed world, this work echoes the findings of ( Ben-David et al, 2011 ) that the prevalence of these factors in the developing world increases the potential reach of their effects.…”
Section: Background and Related Workmentioning
confidence: 99%
“…First, it surfaces key computer security threats and opportunities that we believe ODK deployment architects should consider. Second, it expands on other threat modeling work in ICTD (e.g., ( Ben-David et al., 2011 , Corrigan-Gibbs and Chen, 2014 , Reaves et al., 2015 )) and provides a data point for threats that might arise for ICTD applications.…”
Section: Odk and Computer Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…They described in detail the techniques this malware family used and confronted them with current state-of-the-art static and dynamic code-analysis techniques forAndroid applications.Additionally, several authors investigated the holistic security of mobile money applications including mobile banking, mobile wallets, and mobile payment apps. Reaves et al [46] performed a comprehensive analysis of branchless banking applications. They discovered vulnerabilities using the Common Weakness Enumeration (CWE) classification system and showed that six of the seven applications fail to preserve the integrity of their transactions.…”
Section: Related Workmentioning
confidence: 99%
“…The development of branchless banking will result in potential benefits to stakeholders in many different forms, such as a program that is more effective for social benefits, an increasing number of payment for electricity and water bills, and a better return for bank loan (Ivatury 2006, Diniz et al 2009, Jayo et al 2012. Branchless banking brings much-needed financial services to the unbanked in the developing world (Reaves et al 2015). Ansong et al (2015), for instance, argue that the disproportionate growth of physical/traditional branch banking leads to disparities in the spatial distribution of bank branches.…”
mentioning
confidence: 99%